0021 RNA Sequencing Reveals Transcriptomic Changes in Individuals with Insomnia. (27th May 2020) - Mithani, S; Yun, S; Pattinson, C; Kim, H; Guedes, V; Fink, A; Weljie, A; Gehrman, P; Gill, J
Abstract: Introduction: Insomnia affects 10–20% of the US population and is associated with negative health and psychosocial sequelae. Despite the public health impact of insomnia little is known about its underlying molecular mechanisms. The purpose of this study is to examine differentially expressed genes in 15 patients with chronic insomnia and age- and sex-matched good sleepers (n=15). Methods: We performed total RNA-seq on 30 whole blood samples collected at 09:00 at 150 bp paired-ends on the Illumina NovaSeq-6000 platform. Alignment was performed using the STAR version 2.7.2a software on the human reference genome (GRCh38). Differential gene expression analysis was performed using DESeq2 version 1.24.0. Pathway analysis was performed using IPA, release 2019-08-30. Results: An average of 86.7 million paired end reads per sample were sequenced. We found that 289 genes were differentially expressed in insomnia patients with a log fold change (LFC) ±0.50 and had a FDR p-value < 0.05. Top dysregulated genes include CSMD1 (L2FC=-2.78; p=1.35E-06), DUX4L9 (L2FC=3.40; p=2.81E-06) and GRM4 (L2FC=2.45; p=4.50E-05). Among the functionally relevant genes, CSMD encodes a complement control protein that is known to participate in the complement activation and inflammation in the developing central nervous system. UTS2 (L2FC=1.778; p=8.94E-06) is involved in regulation of orexin A and B activity and rapid eye movement during sleep. Ingenuity Pathway Analysis revealed 3 associated networks: Hematological, Hereditary Disorder, Organismal Injury and Abnormalities (score: 46), Developmental, Hereditary Disorder, Metabolic Disease (score: 43), and Cell Cycle, Cell mediated Immune Response, Cellular Development (score: 43). Conclusion: Overall, our study revealed dysregulated genes in individuals who suffer from insomnia. Notably, dysregulation of these functionally relevant genes could impair functional brain connectivity and synaptic function. Further investigation of these biological pathways will be useful to elucidate the pathogenesis of insomnia and identify novel biomarkers or drug targets for developing improved diagnostics and therapeutics. Support: National Institutes of Nursing Research, Graduate Partnership Program